A study on the mycobacterial burden and phenotypic drug resistance pattern with reference to the GeneXpert Cycle Threshold values in pulmonary tuberculosis - Kashyap, Bineeta; Sarkar, Krishna; Singh, Kapil; Hyanki, Puneeta (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Tuberculosis (TB) remains a significant global health challenge. Early and accurate diagnosis is crucial to prevent further transmission. The present study aimed to correlate cycle threshold values with smear microscopy and culture positivity, and determine cut-off cycle threshold values for levels of smear grade and culture positivity. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Forty presumptive cases of pulmonary TB were included and subjected to Ziehl- Neelsen stain, culture on Lowenstein Jensen media, CBNAAT and drug susceptibility testing for first line anti-tubercular drugs. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Our study predicts 3+, 2+, and 1+ sputum smear grade at a cut-off of Ct value ≤ 16.74, ≤19.68, and ≤ 22.32 respectively. A strong positive correlation was found between time to culture positivity and Ct value. A cut-off of Ct value ≤22.32 predicts culture positivity with a sensitivity of 92%, and a specificity of 67%. None of the isolates showed rifampicin resistance by 1% proportion method. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Understanding the appropriate utilization of CBNAAT Ct values and their correlation with smear microscopy grade, culture, and drug susceptibility testing can assist clinicians in early identification and prompt initiation of appropriate treatment. This knowledge can contribute to the prevention of drug resistance, reduced transmission, and a decreased disease burden associated with TB.